Beroepsbeserings in Suid-Afrika: strafregtelike en deliktuele aanspreeklikheid - Nel, Pieter Willem (University of the Free State, 2007)
The rights and obligations of the respective parties in the event of an occupational accident, as well as the current processes in the criminal law, law of delict and labour law, which are frequently subjected to uncertainty by practicing legal practitioners, especially since the promulgation of the Constitution of the Republic of South Africa, have been described in this thesis. It shows the dynamic interaction between the criminal law, law of delict and labour law in the event of an occupational accident, whether at air or sea, a factory, operating theatre, office or underground mine. The thesis consists of an analysis of the respective legal processes regarding liability after an occupational injury in the South African legal system, as well as a comparison with the legal processes in that regard of England, Ontario in Canada and the United States of America, and concludes with proposals to amend shortcomings.

Die regte en verpligtinge van die onderskeie partye by ‘n ongeval in beroepsverband, asook die bestaande prosesse in die strafreg, deliktereg en arbeidsreg, wat dikwels aan onsekerheid by praktiserende regslui onderwerp is, veral sedert inwerkingtreding van die Grondwet van die Republiek van Suid-Afrika, is in die proefskrif uiteengesit. Daarmee word die dinamiese ineenskakeling van die strafreg, deliktereg en arbeidsreg in die geval van die plaasvind van ‘n ongeval, hetsy ten tye van lug- of seevaart, op land in ‘n fabriek, operasieteater, kantoor of ondergronds in ‘n myn, aangetoon. Die proefskrif bestaan uit ‘n uiteensetting van die onderskeie regsprosesse ten opsigte van aanspreeklikheid ná ‘n beroepsbesering in die Suid-Afrikaanse regstelsel, ‘n vergelyking met die regsprosesse van Engeland, Ontario in Kanada en die Verenigde State van Amerika in daardie verband, en sluit af met bepaalde voorstelle ter wysiging van tekortkominge wat in die totale ontleding uitgewys is.
Thesis (LL.D. (Criminal and Medical Law))--University of the Free State, 2007
Keywords: Accident; Code of practice; Common law claim against employer; Delictual claim against wrongdoer; Disablement; Evidentiary burden; Internal discipline; Legal duty; Negligence; Occupational health and safety legislation; Occupational injury; Regulations; Safety standards; Vicarious liability; Compensation commissioner; Employer's liability; Labor laws and legislation; Workers' compensation